2014
DOI: 10.1371/journal.pone.0094697
|View full text |Cite
|
Sign up to set email alerts
|

Use of Targeted Exome Sequencing in Genetic Diagnosis of Chinese Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia is an autosomal dominant inherited disease characterized by elevated plasma low-density lipoprotein cholesterol (LDL-C). It is mainly caused by mutations of the low-density lipoprotein receptor (LDLR) gene. Currently, the methods of whole genome sequencing or whole exome sequencing for screening mutations in familial hypercholesterolemia are not applicable in China due to high cost. We performed targeted exome sequencing of 167 genes implicated in the homozygous phenotype of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Targeted next-generation sequencing, which included library construction, capture, and sequencing, was carried out. Targeted gene enrichment was performed with the GenCap Custom Enrichment Kit according to the GenCap protocol, as described previously [27][28][29] . Captured DNA libraries were sequenced with the Illumina HiSeq.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted next-generation sequencing, which included library construction, capture, and sequencing, was carried out. Targeted gene enrichment was performed with the GenCap Custom Enrichment Kit according to the GenCap protocol, as described previously [27][28][29] . Captured DNA libraries were sequenced with the Illumina HiSeq.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a pressing clinical incentive to develop effective screening methods420 for the early detection of FH. In a previous study, we used whole exome sequencing and TES to identify patients with HoFH and found that these technologies are useful for providing an accurate genetic diagnosis in patients with severe hypercholesterolemia1011. In the present work, we have analyzed 20 young patients with severe hypercholesterolemia by either array sequencing or TES.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects attended the atherosclerosis clinic at the Anzhen hospital, Beijing, China, during the period 2003–2015. DNA samples from 12 patients were processed using DNA resequencing array7, samples from 14 patients were processed by targeted exome sequencing10, and samples from 6 patients were processed by both methods. Some probands were reported in previous studies11132526.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations